Programa de ensino para autopreparo de pais e professores como agentes de promoção de comportamentos de estudo em crianças - Christovam, Ana Carolina Camargo (2016)
To Study is a class of behavior as complex as relevant in modern society, and such as, should be taught to children and teenagers in order to promote adequate repertoires for this process to occur effectively and autonomously. Studies developed with the objective of training educators to promote appropriate behavior studies indicate the importance of this kind of initiative; access opportunities of this kind, however, is limited to subjects participating in these studies. Based on the teaching programming as established procedure for the preparation of appropriate teaching conditions, and self-preparation as a comprehensively way provide adult education, this study aimed to develop a program to self-prepare of parents and teachers as promoting agents of appropriate behaviors of studies of children and examining the process of development of educational programs itself in terms of favoring and adverse conditions of using represented technology. The development of the program involved: preparation of an teaching program for teacher training (Step I), integration of teacher’s program with one for the preparation of parents, previously produced by other programmer (Step II) and the project writing of the unified program to training parents and teachers (Step III). In terms of the unified program, four terminals objectives were proposed, 22 intermediate objectives of more generic level described in the form of behavioral relations and 731 in more specific levels, corresponding to expressed behavioral relationships synthetically. These objectives were sequenced and arranged in order to compose a 14 modules program, structured in units developed from a regular standard structural and graphic with teaching conditions that promote active participation of learners in each unit, requirements are made in small steps or stages of learning, informative consequences on performance for each evaluation activity (immediate feedback), and considering potential characteristics of learners (whose initial repertoire was defined in the program preparation process). The produced material shall become accessible to the population that may need it through publication and available for review through systematic and controlled applications. With regard to the program preparation process, it was possible to identify conditions that interfered both positively and negatively in the process (programmer's repertoire, access to experts on the subject, self-correcting condition of the program among others) and highlight measures taken in relation to variables that negatively influenced the process, as well needs for further study, process improvement and subsidies for it uses, given its relevance as a tool to produce more effective and socially relevant teaching-learning processes.